2011
DOI: 10.1037/a0022630
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the change in self-stigma following a single session of group counseling.

Abstract: One of the major obstacles to seeking psychological help is the stigma associated with counseling and therapy. Self-stigma, the fear of losing self-respect or self-esteem as a result of seeking help, is an important factor in the help-seeking process. In the present study, college students meeting a clinical cutoff for psychological symptoms participated in 1 session of group counseling that either contained therapist self-disclosure or did not. In general, participants reported significantly less self-stigma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 50 publications
11
105
0
1
Order By: Relevance
“…Likewise, in a study of public and self-stigma on attitudes toward group counseling of 491 college students, self-stigma accounted for 52% of the variance in attitudes toward seeking group counseling, fully mediating the relationship between public stigma and attitudes (Vogel, Shechtman, & Wade, 2010). Among 263 undergraduate students with clinically-significant levels of distress, self-stigma was found to predict interest in continuing versus prematurely terminating counseling (Wade, Post, Cornish, Vogel, & Tucker, 2011). Lastly, Fung, Tsang, Corrigan, Lam, and Cheng (2007) found that greater self-stigma among 108 Chinese individuals with severe mental illness in psychiatric treatment predicted poorer psychosocial treatment attendance and participation.…”
Section: Stigmamentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, in a study of public and self-stigma on attitudes toward group counseling of 491 college students, self-stigma accounted for 52% of the variance in attitudes toward seeking group counseling, fully mediating the relationship between public stigma and attitudes (Vogel, Shechtman, & Wade, 2010). Among 263 undergraduate students with clinically-significant levels of distress, self-stigma was found to predict interest in continuing versus prematurely terminating counseling (Wade, Post, Cornish, Vogel, & Tucker, 2011). Lastly, Fung, Tsang, Corrigan, Lam, and Cheng (2007) found that greater self-stigma among 108 Chinese individuals with severe mental illness in psychiatric treatment predicted poorer psychosocial treatment attendance and participation.…”
Section: Stigmamentioning
confidence: 96%
“…The counselor could directly explore in session how the client's belief that help seekers are "pitiful" or "selfish" has impacted the client's view of him or herself, and explore ways of helping the client to challenge this maladaptive belief. In fact, challenging such beliefs is important, given that greater self-stigma has been linked to poorer treatment adherence and premature termination (Fung, Tsang, & Corrigan, 2007;Wade, Post, Cornish, Vogel, & Tucker, 2011).…”
Section: Implications For Prevention and Practicementioning
confidence: 99%
“…Of 14 published studies to date (Luoma et al, 2008;Link, Struening, et al, 2002;McCay et al, 2007;Shin and Lukens, 2002;Alvidrez et al, 2009;Hammer and Vogel, 2010;Griffiths et al, 2004;MacInnes and Lewis, 2008;Knight, Wykes, and Hayward, 2006;Aho-Mustonen et al, 2011;K. Fung, Tsang, and Cheung, 2011;Lucksted et al, 2011;Wade, Post, et al, 2011;Adler et al, 2009), most utilized cognitive techniques (e.g., psychoeducation, cognitive restructuring) to teach people strategies to better control their thoughts, feelings, sensations, and memories. However, some included elements of acceptance and commitment therapy, which focuses on teaching people to notice, accept, and embrace their thoughts, feelings, and memories, rather than actively work to control them.…”
Section: Intervening With People With Mental Health Concernsmentioning
confidence: 99%
“…Eight of the 14 studies (57 percent) (Luoma et al, 2008;Shin and Lukens, 2002;Hammer and Vogel, 2010;Griffiths et al, 2004;MacInnes and Lewis, 2008;Lucksted et al, 2011;Wade, Post, et al, 2011;Adler et al, 2009) demonstrated significant reductions in self-stigma among those who participated in the intervention. Interventions to reduce self-stigma may be less effective for people with schizophrenia or a psychotic disorder, however; only two of seven studies (28 percent) targeting these populations demonstrated a reduction in self-stigma.…”
Section: Intervening With People With Mental Health Concernsmentioning
confidence: 99%
“…They found that participants' endorsement of public stigma and self-stigma were independently related to attitudes towards seeking counseling. Self-stigma was found to be negatively associated with intention to seek help among college students (Wade et al, 2011). Masuda et al (2009) found that Japanese international students, compared with US college students, reported having greater stigma toward individuals with psychological disorders.…”
Section: Subjective Norms and Perceived Behavioral Controlmentioning
confidence: 99%